Ta’ṡīru al-Wasīlah at-ta‘līmiyyah Barnamaj Macromedia Director ‘ala Mahā rah al-Kalāmu (Baḥṡu Tajriby fī al-Madrasah aṡ-ṡānawiyyah al-Islāmiyyah al-Ḥukūmiyyah 2 Tanah Datar) - Aida Fitria; Eri Ramadona; Ayang Nofitri (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2022)
This study aims to determine the effect of learning media in the Macromedia Director program on speaking skills. This research was conducted at Madrasah Aliyah Negeri 2 Tanah Datar. To find out these problems, the authors use field research using experiments. This research design is a True Experimental Design with the type of The Pre Test-Post-test Control Group Design. After the writer conducted a speaking skills test on students in the experimental and control groups, the maximum result in the experimental group was 98, and the lowest result was 80. Meanwhile, the maximum result in the control group was 87, and the lowest was 40. Therefore, the writer found that the t0 result was more significant than the result of tt, namely the result of t (to = 5.62). Thus, the null hypothesis is rejected, and the reciprocal hypothesis is accepted, intended to look for differences between the results of the first test (results of speaking skills using the usual method) and the results of the second test (results of speaking skills using Macromedia Direct). The conclusion from this study is that the Macromedia Director program influences speaking skills at Madrasah Aliyah Negeri 2 Tanah Datar. Keywords: Learning Media, Macromedia Director, Speaking skills ملخص الغرض من هذا البحث هو لمعرفة تأثير الوسيلة التعليمية ببرنامج مكروميديا ديركطر (Macromedia Director) على مهارة الكلام بحث تجريبي في المدرسة الثانوية الإسلامية الحكومية الثانية تانه داتر. ولمعرفة هذه المشكلة، فاستعملت الكاتبة البحث الميداني بالطريقة التجربية. وتصميم البحث هوTrue Eksperimental Design، بنوعThe Pre Test- Post-test Control Group Design . وبعد ما أن تقوم الكاتبة امتحان مهارة الكلام على التلاميذ في المجموعة التجريبية والضابطة، فتوجد أن أقصى النتائج المجموعة التجريبية 98 وأدنى النتائج 80. وأما أقصى النتائج في المجموعة الضابطة 87 ووأدنى النتائج 40. ولذلك، وجدت الكاتبة أن نتيجة to أكبر من نتيجة tt، فهي نتيجة t (to = 5,62) و نتيجة t في الجدوال t (و في الدراجة 5% = 2,03 و في الدرجة 1%= 2,73) فوجدت الكاتبة أن نتيجة toأكبر من نتيجة tt. و هي2,03<5,62>2,73. بناء على ذلك فالفروض العدمية مردودة والفروض التبادلية مقبولة، المراد بها إيجاد الفرق بين نتيجة امتحان الأول (نتيجة مهارة الكلام بطريقة السمعية والشفهية) ونتيجة امتحان الثانى (نتيجة مهارة الكلام ببرنامج مكروميديا ديركطر). والخلاصة من هذا البحث، يوجد تأثير ببرنامج مكروميديا ديركطر على مهارة الكلام في المدرسة الثانوية الإسلامية الحكومية الثانية تانه داتر. الكلمات الر ئيسية: وسيلة التعليم، مكروميديا، مهارة الكلام